Zooplanktivory in garden eels: benefits and shortcomings of being “anchored” compared with other coral-reef fish - Khrizman, Alexandra; Kolesnikov, Irena; Churilov, Dmitri; Genin, Amatzia (Frontiers in Marine Science, 2024)
Garden eels are elongated zooplanktivorous fish that live in colonies on sandy bottoms, often adjacent to coral reefs. Each eel digs its own burrow, from which it partially emerges to forage on drifting zooplankton while being “anchored” with its tail inside the burrow. Feeding rates and foraging movements were examined in the garden eel Gorgasia sillneri and compared with corresponding measurements carried out as part of this study and by Genin et al. (submitted) with 3 species of “free”, site-attached coral-reef fish. Feeding rates by the garden eels were substantially lower than those of the free fish. In the eels, those rates monotonically increased with increasing current speed up to 20 cm/s, whereas in the free fish maximum rates were observed under moderate flows. A nearly linear increase in feeding rate as function of prey density was observed in both the garden eels and the free fish. However, the slope of that increase in the eels was over an order of magnitude more gradual than that reported for the free fish. The different functional responses of the two fish groups appear to be related to their morphology and maneuverability capabilities. Being elongated, anchored in a burrow and able to modulate body posture according to the flow speed allow the eels high feeding rates under strong currents. The tradeoff, compared with free fish, include limited maneuverability, slower swimming, and smaller foraging volume, rendering the eels’ functional response less efficient to increasing prey density. This cost appears to be compensated by the eels’ ability to occupy sandy, shelter-less bottoms, which in some locations are immensely more abundant than coral-covered rocks, where most planktivorous free fish live.